Re‐exploring tissue regeneration by novel spatial transcriptomics technologies - Wei, Xiaoyu; Li, Hanbo; Du, Jiaxin; Zeng, Xiaoqi; Xu, Xun; Chen, Liang; Gu, Ying (Clinical and translational medicine, 2022)
Applying scRNA-seq to axolotl limb regeneration, researchers discovered a critical cell state transition from connective tissue to blastema cells required for lost tissue reconstruction in a later stage,2 possibly via the epithelial-mesenchymal transition mechanism.3 ATAC-seq data further provided rich chromatin regulatory information and deepened our understanding of the molecular basis of limb regeneration dynamics.4 Single-cell multi-omics have remarkably empowered us with global pictures and networking perspectives, yet they have inherent limitations, too. [...]Chen et al. constructed exquisite spatiotemporal maps of developmental mouse embryos at single-cell resolution.6 Together with the organ atlas of several other species published recently, these spatial transcriptomics profiles provide valuable mechanistic insights into the cell fate specification in developing tissues.7 For clinical research, by focusing on the invasive fronts of intrahepatic cholangiocarcinoma, Wu et al. observed the distinct immune microenvironment that may promote tumour invasion.8 Ou et al. found unique immune cell types enriched in tumour areas with different metabolic activity.9 By analyzing neighboring cell composition from spatial transcriptomics data, Cong et al. identified a specific macrophage subgroup for SARS-CoV-2 clearance and inflammation resolution10 (Figure 1). [...]the accomplishment of spatial transcriptomics from 2D to 3D will provide a complete picture of the research subject at the tissue, cell, and molecular levels.